Calcium montmorillonite as a potential carrier in the release of bisphosphonates. (31st January 2022) - Sandomierski, Mariusz; Zielińska, Monika; Adamska, Katarzyna; Patalas, Adam; Voelkel, Adam
Abstract : There is a strong need to search for more effective bisphosphonate carriers which will lead to their increased bioavailability for bone tissue engineering. Abstract : There is a strong need to search for more effective bisphosphonate carriers which will lead to their increased bioavailability for bone tissue engineering. Montmorillonite and calcium montmorillonite were used as risedronate carriers in this work. It was assumed that the high affinity of bisphosphonates to divalent ions (especially calcium) would lead to high drug sorption and then, as a result of ion exchange under the influence of body fluids, the drug would be released. The assumptions turned out to be correct, which were proved using methods such as EDS mapping (to confirm the calcium incorporation and drug sorption), inverse gas chromatography (to examine the surface activity) and UV-VIS spectroscopy (to determine the risedronate sorption and release profiles). A very high degree of drug release (92%) was obtained for calcium montmorillonite compared to other reports on risedronate carriers.